High-Quality Genomes and High-Density Genetic Map Facilitate the Identification of Genes From a Weedy Rice - Li, Fei; Han, Zhenyun; Qiao, Weihua; Wang, Junrui; Song, Yue; Cui, Yongxia; Li, Jiaqi; Ge, Jinyue; Lou, Danjing; Fan, Weiya; Li, Danting; Nong, Baoxuan; et al. (Frontiers in Plant Science, 2021)
Genes have been lost or weakened from cultivated rice during rice domestication and breeding. Weedy rice (Oryza sativa f. spontanea) is usually recognized as the progeny between cultivated rice and wild rice and is also known to harbor an gene pool for rice breeding. Therefore, identifying genes from weedy rice germplasms is an important way to break the bottleneck of rice breeding. To discover genes from weedy rice germplasms，we constructed a genetic map based on whole-genome sequencing of a F2 population derived from the cross between LM8 and a cultivated rice variety. We further identified 31 QTLs associated with 12 important agronomic traits and revealed that ORUFILM03g000095 gene may play an important role in grain length regulation and participate in grain formation. To clarify the genomic characteristics from weedy rice germplasms of LM8, we generated a high-quality genome assembly using single-molecule sequencing, Bionano optical mapping, and Hi-C technologies. The genome harbored a total size of 375.8 Mb, a scaffold N50 of 24.1 Mb, and originated approximately 0.32 million years ago (Mya) and was more closely related to Oryza sativa ssp. japonica. and contained 672 unique genes. It is related to the formation of grain shape, heading date and tillering. This study generated a high-quality reference genome of weedy rice and high-density genetic map that would benefit the analysis of genome evolution for related species and suggested an effective way to identify genes related to important agronomic traits for further rice breeding.